2012
DOI: 10.1074/jbc.m112.387241
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Interprotein Phosphorylation between Two-hybrid Histidine Kinases Controls Myxococcus xanthus Developmental Progression

Abstract: Background: His-Asp phosphorelay proteins can be components of complex signaling systems. Results: Two hybrid histidine kinases, EspA and EspC, form a signaling complex; EspA phosphorylates both receiver modules to regulate proteolytic turnover of a regulatory protein. Conclusion:Two hybrid histidine kinases are integrated by inter-and intra-histidine aspartate phosphotransfer. Significance: A novel His-Asp phosphorelay signal transduction mechanism was identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(69 citation statements)
references
References 65 publications
3
66
0
Order By: Relevance
“…The Esp signaling system negatively regulates MrpC stability (see Fig. S1 in the supplemental material) to delay M. xanthus development (43) and has been proposed to do so by activating a protease or protease targeting factor to stimulate MrpC turnover (47). However, the signal(s) sensed by the Esp system is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Esp signaling system negatively regulates MrpC stability (see Fig. S1 in the supplemental material) to delay M. xanthus development (43) and has been proposed to do so by activating a protease or protease targeting factor to stimulate MrpC turnover (47). However, the signal(s) sensed by the Esp system is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Signal intensities were quantified using Multi-Gauge (Fujifilm) software. Protein half-lives were calculated assuming a firstorder kinetic degradation reaction as described previously (47). Signal intensities, after subtracting the background, were normalized to the relevant intensity at t ϭ 0, and the natural log of the resulting values was plotted versus minutes after nutrient, chloramphenicol, or protease inhibitor/sonication treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Protein half-lives were calculated assuming a first-order kinetic degradation reaction, as described previously (48). Signal intensities, after subtracting background, were normalized to the relevant intensity at t ϭ 0, and the natural log of the resulting values was plotted versus minutes after chloramphenicol (200 g/ml) treatment, as described previously (5).…”
Section: Methodsmentioning
confidence: 99%
“…Recent in vitro studies showed that the transmitter domain of EspA transfers a phosphoryl group to its own receiver domain (94). Furthermore, the transmitter domain of EspA, but not the transmitter domain of EspC, is capable of transferring a phosphoryl group to the receiver domain of EspC (94).…”
Section: Regulators Of the Timing Of Sporulationmentioning
confidence: 99%
“…Recent in vitro studies showed that the transmitter domain of EspA transfers a phosphoryl group to its own receiver domain (94). Furthermore, the transmitter domain of EspA, but not the transmitter domain of EspC, is capable of transferring a phosphoryl group to the receiver domain of EspC (94). This result and the similarity of the early sporulation phenotypes of the espA and espC mutants (92,93) suggest that EspA and EspC form a signaling unit that inhibits sporulation until the proper time in fruiting body development.…”
Section: Regulators Of the Timing Of Sporulationmentioning
confidence: 99%